How Successful Are Residents and Fellows at Quality Improvement?. Issue 4 (July 2020) - Eden, Elizabeth L.; Harrington, Terence; Chen, Ling-Wan; Chelluri, Lakshmipathi; Higgins, Linda W.; Freel, Jennifer A.; DeKosky, Allison; Bump, Gregory M.
ABSTRACT: Background: Nationally, there is an expectation that residents and fellows participate in quality improvement (QI), preferably interprofessionally. Hospitals and educators invest time and resources in projects, but little is known about success rates or what fosters success. Purpose: To understand what proportion of trainee QI projects were successful and whether there were predictors of success. Methods: We examined resident and fellow QI projects in an integrated healthcare system that supports diverse training programs in multiple hospitals over 2 years. All projects were reviewed to determine whether they represented actual QI. Projects determined as QI were considered completed or successful based on QI project sponsor self-report. Multiple characteristics were compared between successful and unsuccessful projects. Results: Trainees submitted 258 proposals, of which 106 (41.1%) represented actual QI. Non-QI projects predominantly represented needs assessments or retrospective data analyses. Seventy-six percent (81/106) of study sponsors completed surveys about their projects. Less than 25% of projects (59/258) represented actual QI and were successful. Project category was predictive of success, specifically those aimed at preventive care or education. Conclusion: Less than a quarter of trainee QI projects represent successful QI. Implications: Hospitals and training programs should identify interventions to improve trainee QI experience.